Epidemiology of Trauma Caused by Traffic Accidents in Patients Admitted to Imam Khomeini Hospital in Urmia During 2017-2022 - Rasul Bidel Nikoo; Shila Hasanzadeh; Mohamad Jebraeily; Naser Masoudi; Bahlol Rahimi; Farshad Faghisolouk (Tehran University of Medical Sciences, 2024)
Background and Aim: Traffic accidents in Iran are one of the main causes of mortality and morbidity, identifying the factors related to these accidents can be useful in the prevention and proper management of traffic accidents. The purpose of this study was to determine the epidemiology of trauma caused by traffic accidents in Imam Khomeini hospital in Urmia during 2017-2022. Materials and Methods: The current research is a cross-sectional descriptive study that was conducted on patients hospitalized due to traffic accidents in Imam Khomeini hospital in Urmia for five years. The required data included demographic characteristics and information of the injured (role of the injured, time of the accident, location of the accident, type of vehicle, damaged area, and condition of the injured during discharge), which was extracted from the trauma registration system of Urmia University of Medical Sciences. ​ After collecting the data, it was entered into SPSS 16 software and described through frequency distribution table and central and dispersion indices Results: In this study, out of 2086 injured cases, 74.40% (1552 people) were male. The average age of the injured was 34.49 ± 18.47 years. The type of accidental vehicle of most of the injured was motorcycle with 56.70% (998 cases). The most injured were drivers with 52.73% (1100 cases) and among them 57.45% (632 people) were motorcycle riders. 34.08% (711 cases) of injuries to body parts were in the head, neck and face. Conclusion: The results of this research showed that most of the injured in traffic accidents are young motorcycle drivers and the most injuries were related to the head and neck area. Therefore, by knowing the risk factors and the impact of each of them on the outcome of traffic accidents, it is necessary to carry out appropriate interventions to prevent the risky behaviors of young drivers and create a culture of observing safety tips. Also, in the health system, the necessary preparations in terms of manpower and medical equipment should be made to manage the treatment of injuries caused by traffic accidents.